Armazenamento in vitro de ipê amarelo - Faria, Camila Vitória Nunes de (2017)
Handroanthus serratifolius (Vahl) S. O. Grose, is a threatened species due to excessive deforestation and disorderly occupation of the Cerrado. Thus, it is important that techniques are developed in order to preserve species that occur in this biome as is the case of yellow ipe. For this, several techniques are used varying the period of conservation in which the material will be preserved. Among these techniques, we can highlight the production and storage of synthetic seeds, slow growth and cryopreservation that correspond to short, medium and long storage periods, respectively. The objective of this work was to carry out the conservation of H. serratifolius in these different time periods and to study the regeneration and development after storage of these plants. For the synthetic seeds, it was evaluated the effect of 0.25μM of NAA and BAP (0; 0.5; 1.0; 2.0; 4.0; 8.0 μM) in WPM medium on the regeneration of lateral buds of yellow ipê during 30 days. After that, the constitution of the capsules of the synthetic seeds was evaluated through the WPM or WPM/2 medium variation and the percentage of sodium alginate (2, 3 and 4%) for 30 days. For the storage of synthetic seeds, a pre-treatment with sucrose solution at the concentrations of 0, 25, 50 and 75 grams of sucrose was carried out for 16 hours under stirring. Subsequently, the seeds were stored at 8, 15 and 25 ºC in the dark and were evaluated every 15 days for 2 months. For the slow growth, nodal segments were inoculated into WPM medium with different concentrations of sucrose (30, 45 and 60 grams) and placed at 8 and 15 °C for 6 months and monthly the segments were subcultured. For these experiments, the percentage of regeneration, number of shoots, number of leaves, callus formation and oxidation were evaluated. For cryopreservation, droplet vitrification and PVS2 vitrification were tested and the permanence time in PVS2 was evaluated by varying the times in (0, 30, 60, 90 and 120 minutes) and (0, 15, 30, 45, 60, 75 And 90 minutes) respectively. After 30 days the regeneration percentage was evaluated. The best percentage of H. serratifolius nodal segment regeneration was in WPM culture medium with 0.25 μM NAA and 1.0 μM BAP. It was possible to produce synthetic seeds of H. serratifolius from nodal segments and the use of 3% sodium alginate matrix dissolved in half strength WPM medium is indicated. The storage of synthetic seeds is feasible for 56 days, at a temperature of 15 ºC, mainly with preculture in a liquid medium containing 0.25M of sucrose. The cryopreservation of H. serratifolius nodal segments was 53.3% after exposure to the PVS2 vitrification solution for 15 minutes. It is possible to store nodal segments of H. serratifolius for 6 months at 15 ºC with the survival of 70% with the addition of 60g of sucrose.